KETIDAKADILAN BAGI MASYARAKAT MISKIN DALAM AKSESIBILITAS JAMINAN KESEHATAN NASIONAL DI KOTA BANDUNG - Abu Huraerah; Rudi Martiawan; Yaya Mulyana (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The study aims to describe procedural inequity, social inequity and political inequity for the poor in the accessibility to the Indonesian National Health Insurance. This study uses a qualitative method. Meanwhile, data collection uses in-depth interview, observation, and document study. Data analysis steps consist of data reduction, data display, and conclusion drawing and verification. Procedural inequity was shown the invalid data collection process of the poor, so that they are not recorded as beneficiaries (PBI/Penerima Bantuan Iuran) or participants of the Social Security Management Agency of Health (BPJS/Badan Penyelenggara Jaminan Sosial-Kesehatan). Social inequity was shown to be unclear in the eligibility of the poor, which resulted in them having difficulty getting as beneficiaries. Meanwhile, political inequity has shown that there are marginalized the poor. Limited budget allocation causes the power elite to prioritize the poor who are near the power elite. Even though, they have the right to get a national health insurance program.